Peningkatan Kemampuan Bahasa Inggris Melalui Pelatihan IELTS Online Dengan Web IELTS Online Test (IOT) dan Rekaman YouTube - Rhischa Assabet Shilla; Nadia Faradhillah; Nurul Husnah Mustika Sari; Arditya Prayogi (Madani : Indonesian Journal of Civil Society, 2025)
This community service activity aimed to enhance participants' English language proficiency through an online IELTS training program using Web IELTS Online Test (IOT) tools and YouTube recordings. The program addressed the need for accessible and flexible learning options for students and faculty members seeking to pursue higher education abroad. Delivered via Zoom for 12 sessions and supported by the Web IELTS Online Test platform, the training provided personalized resources, tracked participants' progress, and included recorded sessions on a private YouTube channel for self-paced review. The Service Learning (SL) method was employed, engaging participants in a cycle of planning, implementation, and reflection to tailor the process to their needs. The program involved 10 participants, consisting of Grade 3 students from MAN IC Pekalongan and faculty members from UIN. Pre-test results highlighted gaps in the four IELTS skills: listening, reading, writing, and speaking, which were targeted throughout the program. Post-test results showed an average improvement of 1.0 band in listening, 0.5 in reading, 0.5 in writing, and 0.5 in speaking. Although only 40% achieved their target scores, 80% experienced an increase in their overall score, and 20% showed specific skill improvements. These results suggest that integrating digital tools in online training enhances language learning outcomes and supports participants in overcoming learning challenges. This program has implications for broader adoption in similar contexts, emphasizing the role of accessible online learning environments in academic readiness.